Searching for an ecological indicator based on plant functional diversity along a climatic gradient - Batista, Melanie Köbel, 1989- (2012)
Tese de mestrado. Biologia (Ecologia e Gestão Ambiental). Universidade de Lisboa, Faculdade de Ciências, 2012